Shari’ah compliant liquid commodity market : {An expositional study on Bursa Suq al-Sil’ah in Malaysia} / Abdul Azeez Maruf Olayemi ... [et al.] - Hasan, Aznan; Ibrahim, Uzaimah; Buang, Ahmad Hidayah (Faculty of Business and Management, 2015)
One of the major challenges before the emerging Islamic financial Institutions is the dearth of Shariah compliant money market platform for the management of their liquidity. However, a viable panacea to the problem has been developed in Malaysia. One of the measures that were taken for the solving of the problem in the country was the creation of Bursa Suq al-Sil'ah which is a Shariah compliant liquidity commodity market. The market is tremendously efficient and it can form a model for other countries. This paper submits that the creation of a similar commodity market in the emerging jurisdictions will mitigate the problem of Shariah compliant liquidity management to a great extent. The study adopts Shariah method in its analysis in view of buttressing the mechanism of Bursa Suq al-Sil‟ah as a model for the emerging jurisdiction.